2012
DOI: 10.1121/1.3692243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsing of a target tone on the ability to hear it out in different types of complex sounds

Abstract: Judgments of whether a sinusoidal probe is higher or lower in frequency than the closest partial ("target") in a multi-partial complex are improved when the target is pulsed on and off. These experiments explored the contribution of reduction in perceptual confusion and recovery from adaptation to this effect. In experiment 1, all partials except the target were replaced by noise to reduce perceptual confusion. Performance was much better than when the background was composed of multiple partials. When the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Bernstein and Oxenham (2003), using a method in which the target harmonic was pulsed on and off, suggested that the upper limit was somewhat higher. However, the results using this method may have been affected by adaptation and release from adaptation (Moore et al, 2009a;Moore et al, 2012). Assuming that no harmonics above the 8th are resolved, the worsening in F0DLs with increasing N from 9 to 11 presumably reflects a decrease in the ability to use TFS information.…”
Section: Resultsmentioning
confidence: 90%
“…Bernstein and Oxenham (2003), using a method in which the target harmonic was pulsed on and off, suggested that the upper limit was somewhat higher. However, the results using this method may have been affected by adaptation and release from adaptation (Moore et al, 2009a;Moore et al, 2012). Assuming that no harmonics above the 8th are resolved, the worsening in F0DLs with increasing N from 9 to 11 presumably reflects a decrease in the ability to use TFS information.…”
Section: Resultsmentioning
confidence: 90%
“…It is usually assumed that only harmonics up to about the eighth are resolved [51,52], although the exact upper limit is still debated. Bernstein and Oxenham [53] proposed that harmonics up to about the 10th could be resolved, although the method used by them to determine the limits of resolution has been questioned [54,55].…”
Section: The Pitch Perception Of Complex Tones For Normal-hearing Submentioning
confidence: 99%
“…The resolvability of individual components within a harmonic complex can, to some extent, be measured behaviorally (Moore et al, 1984). But focusing only on resolvability misses the possibility that components may also be hidden within complexes by informational masking; they can be made more salient by mistuning (Moore et al, 1986), or by pulsing of a probe tone (Bernstein and Oxenham, 2003;Moore et al, 2012), in a strategy similar to the one tried in experiment 3 by pulsing a complex probe before a complex mixture. Future research could examine whether the resolvability of the complex mixtures used in the present study, when measured behaviorally in this manner, agrees with predictions of resolvability from rate-place models.…”
Section: Discussionmentioning
confidence: 99%